Exogenous silicon alleviates the adverse effects of cinnamic acid-induced autotoxicity stress on cucumber seedling growth - Lyu, Jian; Jin, Ning; Meng, Xin; Jin, Li; Wang, Shuya; Xiao, Xuemei; Liu, Zeci; Tang, Zhongqi; Yu, Jihua (Frontiers in Plant Science, 2022)
Autotoxicity is a key factor that leads to obstacles in continuous cropping systems. Although Si is known to improve plant resistance to biotic and abiotic stresses, little is known about its role in regulating the leaf water status and mineral nutrient uptake of plants under autotoxicity stress. Here, we used cucumber seeds (Cucumis sativus L. cv. ‘Xinchun No. 4’) to evaluate how exogenous Si (1 mmol L-1) affected the leaf water status, mineral nutrient uptake, N metabolism-related enzyme activities, root morphology, and shoot growth of cucumber seedlings under 0.8 mmol L-1 CA-induced autotoxicity stress. We found that CA-induced autotoxicity significantly reduced the relative water content and water potential of leaves and increase their cell sap concentration. CA-induced stress also inhibited the absorption of major (N, P, K), minor (Ca, Mg), and trace elements (Fe, Mn, Zn). However, exogenous Si significantly improved the leaf water status (relative water content and water potential) of cucumber leaves under CA-induced stress. Exogenous Si also promoted the absorption and accumulation of mineral elements by seedlings under CA-induced stress and alleviated the CA-induced inhibition of N metabolism-related enzyme activities (including nitrate reductase, nitrite reductase, glutamine synthetase, glutamate synthase, glutamate dehydrogenase). Moreover, exogenous Si improved N uptake and utilization, promoted root morphogenesis, and increased the growth indexes of cucumber seedlings under CA-induced stress. Our findings have far-reaching implications for overcoming the obstacles to continuous cropping in cucumber cultivation.